Self reflection practices of dhikr in daily life and ikhlas - Murdipi, Rafiqa (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
Teaching and research of mainstream economics and management has been based on neoclassical economics thought. It assumes Homo Economicus, where human being behaves in a self-interested manner to maximise profit and utility. With the assumption, capital owner thinker with appropriate incentive for managers and workers to maximise profit and share price. Islamic economics and management as practised in the Kulliyyah of Economics and Management Sciences has transformed the assumptions and values that are not in accordance with Islamic worldviews. Homo Islamicus that behaves in accordance with Islamic principles and human values, which include justice and cooperation is introduced. These values will drive sustainable development with the internalisation of social cost and benefit in decision making. However, greater efforts are required for the Kulliyyah to be released from the shackle of neoclassical economics.